(untitled) (International Journal of Engineering and Computer Science, 2024)
In a world where 95% of cybersecurity breaches are due to human error, and a rapidly evolving cybersecurity landscape, the effectiveness of employee’s proper security awareness stands as a pivotal concern [1]. Especially when the employees are the first line of defense for any organization. This highlights the importance of having robust cybersecurity awareness that is dynamic to face the ever-changing threats in the world. However, traditional employee security awareness training programs often fall short, perceived as dull, ineffective, and unable to keep pace with the dynamic cybersecurity landscape [2]. These shortcomings not only diminish engagement but also lead to decreased knowledge retention, rendering employees more vulnerable to cyber threats.